Plasma deposition and surface characterization of oligoglyme, dioxane, and crown ether nonfouling films - Johnston, Erika E (Langmuir : the ACS journal of surfaces and colloids, 2005)
Plasma-deposited PEG-like films are emerging as promising materials for preventing protein and bacterial attachment to surfaces. To date, there has not been a detailed surface analysis to examine the chemistry and molecular structure of these films as a function of both precursor size and structure. In this paper, we describe radio-frequency plasma deposition of a series of short-chain oligoglymes, dioxane, and crown ethers onto glass cover slips to create poly(ethylene glycol)-like coatings. The resultant films were characterized by X-ray photoelectron spectroscopy (XPS), time-of-flight secondary ion mass spectrometry (TOF-SIMS), dynamic contact angle goniometry, and radiolabeled fibrinogen adsorption. Detailed analysis of the high-mass (120-300 m/z) TOF-SIMS oligoglyme film spectra revealed six classes of significant fragments. Two new models are proposed to describe how these fragments could be formed by distinct film-building processes: incorporation of intact and fragmented precursor molecules. The models also provide for the incorporation of hydrocarbon--a species that is not present in the precursors but is evidenced in XPS C(1s) spectra of these films. Two additional models describe the effects of incorporating intact and fragmented cyclic precursors